A Study On The Fabrication And Characterization Of Sputtered Cr Doped Zno Thin Film Gas Sensors - al-Hardan, Naif Hammad Misshin (2011)
Zinc oxide (ZnO) and chromium (Cr) doped ZnO thin films were successfully produced by reactive radio frequency co-sputtering of high purity zinc and chromium metal targets. The Cr concentrations were in the range of (1 – 4) atomic percentage. The X – ray diffraction revealed that the ZnO films possessed a polycrystalline structure with a (002) dominant phase grown along the c-axis of the hexagonal structure of the ZnO. The (002) peak was slightly shifted toward higher Bragg angles when the Cr substitutionally replaced the Zn in the ZnO crystals. The films exhibited a uniformly distributed nano grains with a columnar structure.